2021
DOI: 10.1016/j.nicl.2021.102660
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of gray matter volumes and associated gene expression profiles in cognitively-defined Alzheimer’s disease subgroups

Abstract: Highlights Cognitively-defined subgroups among individuals with AD dementia identified. Subgroup gray matter volume patterns were distinct, matching cognitive profiles. Gene-set enrichment analyses revealed gray matter vs gene expression associations. These associations were partly shared between subgroups, and partly unique. Distinct biological drivers may be involved in heterogeneity of Alzheimer’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 71 publications
4
21
1
Order By: Relevance
“…Our group recently confirmed these phenotypes in vivo using a multisite dataset of over 2000 tau-positron emission tomography scans, and we additionally described the existence of a posterior and an asymmetric lateral temporal pattern of tau accumulation [6] (Figure 1A). Patterns similar to these latter phenotypes have been described in studies probing neurodegenerative profiles of late-onset AD cases with impairments in specific cognitive domains [3]. In our study, we did not find one dominant tau pattern that fits the description of 'typical' AD.…”
Section: The Landscape Of Clinical Heterogeneity In Adsupporting
confidence: 85%
“…Our group recently confirmed these phenotypes in vivo using a multisite dataset of over 2000 tau-positron emission tomography scans, and we additionally described the existence of a posterior and an asymmetric lateral temporal pattern of tau accumulation [6] (Figure 1A). Patterns similar to these latter phenotypes have been described in studies probing neurodegenerative profiles of late-onset AD cases with impairments in specific cognitive domains [3]. In our study, we did not find one dominant tau pattern that fits the description of 'typical' AD.…”
Section: The Landscape Of Clinical Heterogeneity In Adsupporting
confidence: 85%
“…Moreover, this approach carries the notion that the typical population likely represents a more homogeneous group that is presumably a more adaptive or optimal state 16 , making it the reference standard for AD research and clinical trials. This is in contrast with recent studies that have demonstrated intragroup variability even within the clinical population of 'typical AD' 17 . Making heterogeneity the object of study requires to move beyond the classic case-control approach and use techniques that address interindividual variation.…”
Section: Introductioncontrasting
confidence: 99%
“…GM density and cortical thickness (CT) obtained from sMRI are two widely used morphometric features. Both GM features respectively constitute multimode features with pathological information, so they have been applied to studies on AD subtypes [ 7 , 8 ]. The GM density for each region-of-interest (ROI) is computed as the sum of GM densities of all voxels within the ROI from the voxel-based morphometry (VBM) maps using statistical parametric mapping (SPM).…”
Section: Introductionmentioning
confidence: 99%